Maternal child-feeding practices and dietary inadequacy of 4-year-old children. (1st September 2015) - Durão, Catarina; Andreozzi, Valeska; Oliveira, Andreia; Moreira, Pedro; Guerra, António; Barros, Henrique; Lopes, Carla
Highlights: Maternal control lowers the probability of low consumption of F&V by children. Higher overt control increases the odds of F&V consumption above recommendations. Pressure to eat increases the odds of dairy consumption above the recommendations. Most maternal practices decrease children's consumption of energy-dense foods. Abstract: This study aimed to evaluate the association between maternal perceived responsibility and child-feeding practices and dietary inadequacy of 4-year-old children. We studied 4122 mothers and children enrolled in the population-based birth cohort – Generation XXI (Porto, Portugal). Mothers self-completed the Child Feeding Questionnaire and a scale on covert and overt control, and answered to a food frequency questionnaire in face-to-face interviews. Using dietary guidelines for preschool children, adequacy intervals were defined: fruit and vegetables (F&V) 4–7 times/day; dairy 3–5 times/day; meat and eggs 5–10 times/week; fish 2–4 times/week. Inadequacy was considered as below or above these cut-points. For energy-dense micronutrient-poor foods and beverages (EDF), a tolerable limit was defined (<6 times/week). Associations between maternal perceived responsibility and child-feeding practices (restriction, monitoring, pressure to eat, overt and covert control) and children's diet were examined by logistic regression models. After adjustment for maternal BMI, education, and diet, and children's characteristics (sex, BMI z-scores), restriction, monitoring, overt and covert control were associated with 11–18% lower odds of F&V consumption below the interval defined as adequate. Overt control was also associated with 24% higher odds of their consumption above it. Higher perceived responsibility was associated with higher odds of children consuming F&V and dairy above recommendations. Pressure to eat was positively associated with consumption of dairy above the adequate interval. Except for pressure to eat, maternal practices were associated with 14–27% lower odds of inadequate consumption of EDF. In conclusion, children whose mothers had higher levels of covert control, monitoring, and restriction were less likely to consume F&V below recommendations and EDF above tolerable limits. Higher overt control and pressure to eat were associated, respectively, with higher possibility of children consuming F&V and dairy above recommendations.